Nanotechnology Enables Novel Modalities for Neuromodulation. Issue 52 (19th October 2021) - Yang, Xiao; McGlynn, Eve; Das, Rupam; Paşca, Sergiu P.; Cui, Bianxiao; Heidari, Hadi
Abstract: Neuromodulation is of great importance both as a fundamental neuroscience research tool for analyzing and understanding the brain function, and as a therapeutic avenue for treating brain disorders. Here, an overview of conceptual and technical progress in developing neuromodulation strategies is provided, and it is suggested that recent advances in nanotechnology are enabling novel neuromodulation modalities with less invasiveness, improved biointerfaces, deeper penetration, and higher spatiotemporal precision. The use of nanotechnology and the employment of versatile nanomaterials and nanoscale devices with tailored physical properties have led to considerable research progress. To conclude, an outlook discussing current challenges and future directions for next‐generation neuromodulation modalities is presented. Abstract : Recent advances in developing novel nanoscale neuromodulation strategies with less invasiveness, improved biointerfaces, deeper penetration, and higher spatiotemporal precision are discussed. The employment of versatile nanomaterials and nanoscale devices with tailored physical properties has led to considerable research progress in nanotechnology‐enabled electrical, optical, chemical, acoustic, and magnetic neuromodulation modalities, and cross‐modal neuromodulation strategies using nanomaterials as energy transducers.